2019
DOI: 10.1016/j.eurox.2019.100073
|View full text |Cite
|
Sign up to set email alerts
|

The impact of IVF on deep invasive endometriosis

Abstract: Objective Ovarian hyper-stimulation during IVF is associated with a significant raise in serum estrogens and one may expect detrimental effects on estrogen-dependent diseases such as endometriosis. However, available evidence from large case series of affected women performing IVF is generally reassuring with the possible exception of women carrying deep invasive lesions. On this basis we deemed important investigating more in depth whether women with deep invasive endometriosis could be a subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Starting IVF with a DE nodule left in place is highly questionable, and especially in women suffering from severe chronic pelvic pain or serious dysmenorrhea. Berlanda et al clearly showed that IVF procedure did not have positive impact on pain symptoms in a retrospective series of 84 patients with DE undergoing IVF cycles [ 44 ]. This strongly suggests that excision surgery should be discussed with infertile women suffering pain symptoms associated to DE to improve their quality of life, as statistical improvement in both sexual- and health-related quality of life is observed after surgery [ 45 ].…”
Section: Deep Endometriosis: Self-limited or Evolving Disease?mentioning
confidence: 99%
See 1 more Smart Citation
“…Starting IVF with a DE nodule left in place is highly questionable, and especially in women suffering from severe chronic pelvic pain or serious dysmenorrhea. Berlanda et al clearly showed that IVF procedure did not have positive impact on pain symptoms in a retrospective series of 84 patients with DE undergoing IVF cycles [ 44 ]. This strongly suggests that excision surgery should be discussed with infertile women suffering pain symptoms associated to DE to improve their quality of life, as statistical improvement in both sexual- and health-related quality of life is observed after surgery [ 45 ].…”
Section: Deep Endometriosis: Self-limited or Evolving Disease?mentioning
confidence: 99%
“…The surgical procedure of rectal shaving in excision of DE nodules was firstly described in 1991 by Donnez [ 48 ] and Reich [ 49 ]. These studies were followed by many others from the same team between 1997 and 2013, with the biggest series so far about 3298 cases [ 15 , 35 , 44 , 50 , 51 , 52 ].…”
Section: Shaving Technique: Surgical Proceduresmentioning
confidence: 99%
“…Nevertheless, it is unclear if a bowel lumen stenosis R50% was systematically ruled out in these women before proceeding with assisted reproductive technologies (ART). In fact, the incidence of severe complications specifically due to the progression of infiltrating colorectal lesions in women without preexisting subocclusion seems limited, despite the temporary hyperestrogenism typical of IVF (3).…”
mentioning
confidence: 99%